Clinical and molecular description of the first Italian cohort of 33 subjects with hypophosphatasia - Cinque, Luigia; Pugliese, Flavia; Salcuni, Antonio Stefano; Trombetta, Domenico; Battista, Claudia; Biagini, Tommaso; Augello, Bartolomeo; Nardella, Grazia; Conti, Francesco; Corbetta, Sabrina; Fischetto, Rita; Foiadelli, Thomas; et al. (Frontiers in endocrinology (Lausanne), 2023)
Hypophosphatasia (HPP) is a rare genetic disease caused by inactivating variants of the ALPL gene. Few data are available on the clinical presentation in Italy and/or on Italian HPP surveys.IntroductionHypophosphatasia (HPP) is a rare genetic disease caused by inactivating variants of the ALPL gene. Few data are available on the clinical presentation in Italy and/or on Italian HPP surveys.There were 30 suspected HPP patients recruited from different Italian tertiary cares. Biological samples and related clinical, biochemical, and anamnestic data were collected and the ALPL gene sequenced. Search for large genomic deletions at the ALPL locus (1p36) was done. Phylogenetic conservation and modeling were applied to infer the effect of the variants on the protein structure.MethodsThere were 30 suspected HPP patients recruited from different Italian tertiary cares. Biological samples and related clinical, biochemical, and anamnestic data were collected and the ALPL gene sequenced. Search for large genomic deletions at the ALPL locus (1p36) was done. Phylogenetic conservation and modeling were applied to infer the effect of the variants on the protein structure.There were 21 ALPL variants and one large genomic deletion found in 20 out of 30 patients. Unexpectedly, NGS-driven differential diagnosis allowed uncovering three hidden additional HPP cases, for a total of 33 HPP subjects. Eight out of 24 coding variants were novel and classified as "pathogenic", "likely pathogenic", and "variants of uncertain significance". Bioinformatic analysis confirmed that all the variants strongly destabilize the homodimer structure. There were 10 cases with low ALP and high VitB6 that resulted negative to genetic testing, whereas two positive cases have an unexpected normal ALP value. No association was evident with other biochemical/clinical parameters.ResultsThere were 21 ALPL variants and one large genomic deletion found in 20 out of 30 patients. Unexpectedly, NGS-driven differential diagnosis allowed uncovering three hidden additional HPP cases, for a total of 33 HPP subjects. Eight out of 24 coding variants were novel and classified as "pathogenic", "likely pathogenic", and "variants of uncertain significance". Bioinformatic analysis confirmed that all the variants strongly destabilize the homodimer structure. There were 10 cases with low ALP and high VitB6 that resulted negative to genetic testing, whereas two positive cases have an unexpected normal ALP value. No association was evident with other biochemical/clinical parameters.We present the survey of HPP Italian patients with the highest ALPL mutation rate so far reported and confirm the complexity of a prompt recognition of the syndrome, mostly for HPP in adults. Low ALP and high VitB6 values are mandatory for the genetic screening, this latter remaining the gold standard not only to confirm the clinical diagnosis but also to make differential diagnosis, to identify carriers, to avoid likely dangerous therapy in unrecognized cases.DiscussionWe present the survey of HPP Italian patients with the highest ALPL mutation rate so far reported and confirm the complexity of a prompt recognition of the syndrome, mostly for HPP in adults. Low ALP and high VitB6 values are mandatory for the genetic screening, this latter remaining the gold standard not only to confirm the clinical diagnosis but also to make differential diagnosis, to identify carriers, to avoid likely dangerous therapy in unrecognized cases.